Surface polarization profile of ferroelectric thin films probed by X-ray standing waves and photoelectron spectroscopy - Le Phuong Hoang; Irena Spasojevic; Tien-Lin Lee; David Pesquera; Kai Rossnagel; Jörg Zegenhagen; Gustau Catalan; Ivan A. Vartanyants; Andreas Scherz; Giuseppe Mercurio (Scientific Reports)
Abstract Understanding the mechanisms underlying a stable polarization at the surface of ferroelectric thin films is of particular importance both from a fundamental point of view and to achieve control of the surface polarization itself. In this study, we demonstrate that the X-ray standing wave technique allows the surface polarization profile of a ferroelectric thin film, as opposed to the average film polarity, to be probed directly. The X-ray standing wave technique provides the average Ti and Ba atomic positions, along the out-of-plane direction, near the surface of three differently strained $$BaTiO_3$$ thin films. This technique gives direct access to the local ferroelectric polarization at and below the surface. By employing X-ray photoelectron spectroscopy, a detailed overview of the oxygen-containing species adsorbed on the surface is obtained. The different amplitude and orientation of the local ferroelectric polarizations are associated with surface charges attributed to different type, amount and spatial distribution of the oxygen-containing adsorbates.